Kuwait : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2010)
The paper gives statistical data on sectoral origin of gross domestic product at current prices and constant prices; expenditure at current market prices and at constant production in Kuwait. It provides data on disposal; and prices of oil and LPG; consumer and wholesale price index; output of major industrial products; population and employment; distribution of employees by economic activity and nationality; summary of government finance, revenue, monetary survey; and financial account reserves and net foreign assets of the financial sector along with other major areas.